Preparation and characterisation of a lamellar hydroxyapatite/polylactic acid composite. (7th February 2019) - Liu, Shanshan; Li, Yuanliang; Sun, Haina; Zhang, Songtao; Zeng, Xiongfeng; Zong, Peixiao; Wan, Yizao; Zuo, Guifu
ABSTRACT: In this study, laminated hydroxyapatite/polylactic acid (HAp/PLA) composites were synthesized through solution intercalation method. The phase composition and micro morphology of the prepared HAp/PLA composites were characterized by X-ray diffraction, Fourier transform infrared spectroscopy and scanning electron microscopy, respectively. The obtained data revealed that intercalated and exfoliated structures were obtained by different HAp contents. Computed tomography result showed that the HAp lamellae distributed well in the PLA matrix and no air-bubble existed in the interface of HAp and PLA. Differential scanning calorimetry and mechanical performance test revealed that the thermal stability and tensile strength were all improved by intercalating of HAp lamellae. Moreover, the degradation experiment confirmed that the 10HAp/PLA showed the slowest degradation rate attributing to the molecular barrier effect of HAp lamellae. Besides that, MTT assay suggested that HAp/PLA composite exhibit excellent biocompatibility, indicating that it may become a promising material for biomedical applications. GRAPHICAL ABSTRACT: